Ingresos y gastos operacionales del Comercial “Almacén Centro Plast” del cantón Babahoyo, en el periodo 2020-2021. - Segura Vinces, Darlin Janeth (2022)
The commercial company "Centro Plast" located on Abdón Calderón and García Moreno streets in the Babahoyo Canton, Los Ríos Province, has as its economic activity the wholesale and retail purchase-sale of household items and plastic items. The objective of this case study is to know the state of the operational income and expenses of the Centro Plast commercial in Babahoyo Canton, through a significant analysis of the 2020 period and the 2021 period. For this reason, the descriptive method was implemented. , and through the analysis it was possible to detect that, in the year 2020, its operating expenses fell much more compared to the year 2021, all this caused the low level of sales, which in turn caused the payment of salaries to decrease and there is staff reduction. This commercial company also acts as a distributor since it sells its merchandise to wholesalers and retailers, distributing it to different parts of the canton as well as the province, making its brand one of the most recognized and consolidated in the sale of household items. and plastic products.